PENGARUH MODEL PEMBELAJARAN BERBASIS MASALAH DAN MOTIVASI BELAJAR TERHADAP KEMAMPUAN MENULIS ARGUMENTASI SISWA SMA FITRA ABDI PALEMBANG - Irwansa Irwansa (Jurnal Pembahsi (Pembelajaran Bahasa Dan Sastra Indonesia), 2017)
The purpuse of this research was to determine model of Problem-Based Learning and Learning Motivation toward writing argumentation’s ability before using the problem-based learning. This research used the method of experimental method. The population of this research is the all students in the tenth grade of SMA Fitra Abdi Palembang with the total number 116 students and the total of the data sample of this research is 68 students. Based on the above, the writer used two-way anova analysis. Besides, the writer also found the result of this research: (1) there was a significant difference in writing ability between student who tought by using problem-based learning and conventional learning. Where the result  was 0,00 it means that the result was lower than significant level (0,05) and (2) there was an interaction effect toward writing argumentation’s  ability where the result of this research is 3,915, it means that higher than Ftab (3,32) with the significant level  (0,05) Keywords: Problem-based learning, motivation, writing argumentation